Analyzing a Unique Controlled Vocabulary: Chiropractic Subject Headings—Past, Present and Future. - Hardy, Sarah B. (Chiropractic History)
In this paper, the author attempts to analyze a distinct library controlled vocabulary. Chiropractic Subject Headings (ChiroSH), in the greater context of the history of medical literature and medical subject headings, the history of chiropractic clinical practice and chiropractic literature, and its use in the Index to Chiropractic Literature (ICL) in particular. Using a variety of sources including journal articles and interviews with ICL indexers, chiropractic librarians, and the current editors of ChiroSH, the author intends to demonstrate the value in developing specialized controlled vocabularies for areas of medical knowledge that go beyond the scope of MeSH, to ultimately enhance the research of students, faculty, practitioners, and the curious.